2019
DOI: 10.3390/w11081535
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Arbuscular Mycorrhizal Fungi (AMF) Communities Colonize Plants Inhabiting a Constructed Wetland for Wastewater Treatment

Abstract: Constructed wetlands (CWs) are biological wastewater treatment systems that comprise several components where plants and associated organisms play an important role in water depuration. Microbial studies emphasize bacterial dynamics, whereas studies of arbuscular mycorrhizal fungi (AMF) are scarce and the functional role of AMF in aquatic and wetland plants is poorly understood. The aim of this study was to analyze the AMF communities colonizing the roots of Canna indica, Canna flaccida, and Watsonia borbonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Wastewater at the inlet and outlet of the CW and the water of the pond can be considered as easily treatable by biological approaches, based on the BOD/COD ratio [28]. These findings are in alignment with what has been reported in literature for the operation of these systems, with a high organic loading in the period with a higher number of overnight stays, which usually occurs in the summer [6,29]. This gives rise to a typical low-medium strength untreated domestic wastewater, concerning its organic and nutrient contents.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Wastewater at the inlet and outlet of the CW and the water of the pond can be considered as easily treatable by biological approaches, based on the BOD/COD ratio [28]. These findings are in alignment with what has been reported in literature for the operation of these systems, with a high organic loading in the period with a higher number of overnight stays, which usually occurs in the summer [6,29]. This gives rise to a typical low-medium strength untreated domestic wastewater, concerning its organic and nutrient contents.…”
Section: Discussionsupporting
confidence: 67%
“…However, its forecasted concentration, based on the concentration of the ionized ammonia detected, the pH of the samples, and the water temperature during the exposures [31], was likely lower than the 48 h LC 50 value and the corresponding 95% confidence interval reported for D. magna of 2.94 (2.70-3.22) mg NH 3 -N/L in sample B [32]. The toxicity of ammonia has been mainly attributed to nonionized ammonia, which is kept in equilibrium with the ionized form [29]. An EC 50 value of 1.5 mg/L NH 3 -N was reported for D. magna and an EC 50 value for NH 4 + -N of 95.2 mg/L was estimated by Villamar et al [33].…”
Section: Ecotoxicological Assessmentmentioning
confidence: 95%
“…These primers amplified, in addition to AMF, also non-AMF sequences to a small extent [28,29,47,48,49,50], like Ascomycota and Basidiomycota with a higher incidence of Ascomycota (14% from all sequences) in our case. However, many studies using these primers have significantly increased our knowledge about AMF communities in various environments [51,52,53,54,55,56]. In our case, more than 86% of the DNA sequences in the control sample and more than 69% in the sludge sample belonged to some group of AM fungi.…”
Section: Discussionmentioning
confidence: 59%
“…Yadav et al [ 89 ] showed that the wetland bed depth has direct significant effect on HMs removal efficiencies in vertical flow CWs. In fact, the removal of Cr, Ni, Cu, Zn and Co increased by 16.6%, 22.9%, 20.4%, 21.5%, and 21.8%, respectively, when the gravel bed depth of CWs was increased from 0.3 to 1.5 m. In addition, the presence of various microorganisms and the initial concentration of HMs also affect plant performance [ 127 ]. The higher HMs concentration in water induces the higher uptake by plants [ 95 ].…”
Section: Discussionmentioning
confidence: 99%